Mechanical behaviour of tangled metal wire devices. (1st March 2019) - Chandrasekhar, Kartik; Rongong, Jem; Cross, Elizabeth
Highlights: Quasi-static experiments reveal slow dynamic effects. Trends in properties similar at low (<20 Hz) and high frequencies (50–400 Hz). Frequency dependence negligible over a broad range of frequencies. Static compression and dynamic strains key factors in defining the performance. Classic Coulomb friction behaviour: mechanical properties only amplitude dependent. Abstract: Tangled metal wire (TMW) devices can be used as damping elements in extreme environments where traditional materials such as viscoelastic polymers deteriorate or become ineffective. Dynamic properties of TMW devices are highly nonlinear because the microstructure consists of coiled metal wires that are compressed together. This paper examines the sensitivity of their dynamic stiffness and damping to loading conditions, in particular, pre-compression, dynamic amplitude and frequency of excitation. Using displacement-controlled experiments, it is shown that properties depend strongly on pre-compression and dynamic amplitude as would be expected in a structure comprising many frictional contact points. Frequency dependence is shown to be negligible over a broad frequency range that encompasses the region of interest for typical machine applications. This work identifies slow dynamic effects, with timescales of the order of around 10 s, which show that quasi-static testing, which is sometimes used for these materials, will not provide accurate estimates of dynamic properties.